Understanding online instructional modeling theories and practices - Zheng, Robert; Ferris, Sharmila Pixy (Gale virtual reference library, 2008)
Focuses on both theoretical and practical aspects of online learning by introducing a variety of online instructional models and best practices that help educators and professional trainers to better understand the dynamics of online learning.